Reply to Professor Levine on Rhetoric and Reality in American Welfare History - Kern, William S. (Journal of Economic Issues (Association for Evolutionary Economics), 2001)
The article replies to professor David Levine's rhetoric and reality in American welfare history. The author largely agrees with Professor Levine's conclusion that the impact of the application of the principles of 1834 on contemporary welfare reform is "far more potent rhetorically than it is in fact" (733) and that "the slowly expanding mild welfare state is here to stay" (741). Levine argues that this is the result of the emergence and persistence of a "New Deal consensus" regarding the responsibility of government to secure macroeconomic stability and individual security that survives from its origin in the 1930s till today. The questions that arise are why this consensus emerged when it did and why it persists. In his paper the author attempts to explain why the reemergence of the rhetoric and practice of welfare reform had occurred, and he argues that an answer could be found in ideas developed by Karl Polanyi in The Great Transformation (1944). It had been argued that the logic of the self-regulating market required the denial of a right to life outside the market. This was affirmed in the passage of the New Poor Law and in the rhetoric and practices of current welfare reform. However, Polanyi's Great Transformation also provided us with an explanation of the factors which underlie the emergence of the New Deal consensus in the 1930s, the persistence of the welfare state, and the largely rhetorical impact of the principles of 1834 on current welfare reforms.
Economics
Keywords: United States; economic conditions - United States; economic history; macroeconomics; public welfare; reforms; welfare economics

Planning and the Politics of Markets: Some Lessons from Financial Regulation in Nepal - Rankin, Katharine N. (International Planning Studies, 2001)
This paper calls for an explicit return to questions about the normative foundations of planning theory and practice. It argues that a simultaneous reading of Karl Polanyi with Friedrich von Hayek can contribute to developing an ethical basis for tempering market rationality with social rationality in the current global economic conjuncture. Empirically, the paper investigates recent initiatives in Nepal to provide social protections (à la Polanyi) through financial market rules. In the face of threats to the progressive legacy in planning practice posed by the prevailing neoliberal orthodoxy, Nepal's targeted lending policies and microcredit programmes offer some optimism about the potential to embed welfare provisions within market regulation, especially when compared to developments in other countries. At the same time, however, the perspectives of rural women explored here through critical ethnography raise key questions about the capacity of these regulations to generate social opportunity and highlight a role for locally situated social criticism in progressive planning practice.
Geography
Keywords: HAYEK; Friedrich A. von (Friedrich August); 1899-1992; Nepal; financial regulation; international planning studies; markets; planning; social protection

Discourses on peace and development - Hettne, B. (Progress in Development Studies, 2001)
Assuming a close relationship between peace and development, this paper analyses a succession of schools of thought in development forming part of three distinct, historically contextualized development and security discourses: the industrialization imperative in the emerging state-system in nineteenth-century Europe, the international concern with global poverty in the bipolar post second world war world and the current meaning of development in a globalized and increasingly chaotic world. The third of these discourses contains major challenges for development theory. The discourses are related to great transformations in political economy, understood in Polanyian terms as tensions between market expansion and societal response.
Peace Studies; Development Studies
Keywords: conflict; development theory; discourse; economic development; market expansion; peace; peace - economic aspects; security

Institutional Investors and Polanyi's Double Movement: A Model of Contemporary Currency Crises - Harmes, Adam (Review of International Political Economy, 2001)
This article constructs a model of contemporary currency crises which incorporates the role played by institutional investors and the dynamics associated with Karl Polanyi's notion of the "double movement." Polanyi's double movement, and its recognition of the need to integrate politics with economics, is used to explain why so many governments are prone to pursue policies that lead to a speculative attack against fixed exchange rates and why virtually every modern fixed exchange rate regime has ended in crisis. Evidence on the short-term and herd behaviour of institutional investors is used to explain why contemporary currency crises do not appear to be justified by underlying economic fundamentals and why these crises do so much more damage than their earlier counterparts. The model is then applied to the 1992 European Exchange Rate Mechanism crisis, the 1994 Mexican peso crisis and the 1997 East Asian crisis. While recognizing that variations exist in the specific circumstances of each episode, the argument of this article is that the progression of events do seem to conform to the model presented.
Political Science
Keywords: corporate finance and governance; double movement; economic development; financial instruments; financial markets; foreign exchange; institutional investors; international linkages to development; international monetary arrangements and institutions; international political economy; non-bank financial institutions; pension funds; role of international organizations; saving and capital investment

Regulationist and Autopoieticist Reflections on Polanyi's Account of Market Economies and the Market Society - Jessop, Bob (New Political Economy, 2001)
This article re-interprets and develops Polanyi’s substantive institutionalist analysis of capitalist market economies and the market society in the light of two more recent approaches to the same issues. These are the Parisian ‘regulation school’ on contemporary capitalism and systems-theoretica l accounts of the modern economy. All three regard the capitalist economy (or, for autopoietic systems theory, the market economy) as an operationally autonomous system that is nonetheless socially embedded and needful of complex forms of social regulation. For each, an adequate account of economic activities should explore how they are related to the wider social environment; how they are embedded in a wider nexus of social institutions; how the latter assist in reproducing the capitalist (or market) economy; and how their development is coupled to that of these and other environing institutions. There are also some important differ- ences among these approaches, however, which enable an exploration of their respective limitations and also provide useful bases for further theoretical and empirical research. Thus, after presenting these three perspectives on the institutedness and embeddedness of economies. I consider some basic problems in analysing the improbable stability and reproducibility of the capitalist economy, paying particular attention to governance and meta-governance.
Sociology; Political Science
Keywords: capitalism; economics; market society; political economy; regulation school; substantive approach

Une lecture de Karl Polanyi - Maucourant, Jérôme (L'Économie politique, 2001)
Vouloir débattre de questions d’économie politique, comme la présente revue et toute l’oeuvre de Karl Polanyi (1) nous y invitent, semble relever, à l’aube du XXIe siècle, d’une absolue gageure. Sur le plan académique, l’économie politique s’est métamorphosée en une « science » économique fondée sous le double sceau de l’individualisme méthodologique et de l’affirmation d’une dichotomie totale entre faits et valeurs. A l’inverse, l’anthropologie de Polanyi se fonde sur un socialisme humaniste qui fut nourri par des lectures de Karl Marx et un ancien projet de « sociologie chrétienne ». Sur le plan théorique et politique, Karl Polanyi cherche à justifier une conception de la démocratie comme contrôle social de notre devenir. Dès 1922, chose qui est peu soulignée, il tente de penser un modèle de socialisme décentralisé pour répondre à ce qu’il considère comme l’impasse du libéralisme et l’erreur que constitue la planification centralisée.
Economics; Political Science

Le travail, la servitude et la vie. Avant Marx et Polanyi, Eugène - Vatin, François (Revue du MAUSS, 2001)
Sociology
Keywords: France; MARX; Karl; 1818-1883; history; labour